Ex Post Control and Steering of Government Agencies: A Comparative Analysis of Lithuania and Romania - Vitalis NAKROŠIS; Žilvinas MARTINAITIS; Adrian HUDREA; Dan BALICA (Transylvanian Review of Administrative Sciences, 2016)
The article analyzes the management of government agencies in Central and Eastern Europe. It seeks to explain the similarities and differences of agency control and steering in the two selected post-communist countries: Lithuania and Romania. Our comparative research is based on desk research and statistical analysis of the COBRA data. In contrast to Romania whose agency management has gravitated around the Weberian-style model, Lithuania has shifted its agency landscape more towards the NPM-style management as a result of more extensive and centralized managerial reforms in the 2000s. This is attributable to a more systemic and top-down approach to result-oriented management in the latter country. Despite the adoption of NPM-inspired reforms in Romania and Lithuania, agencies in these countries do not exhibit systematic relationships between the level of autonomy and ex post control, which can be related to incomplete implementation, differences in the selected management instruments, and certain agency specifi cities.